Factors Affecting the Efficiency of Phototherapy Devices for Treating Neonatal Jaundice - Pasirtpanit, Suthat; Surin, Prayoon; Wiwatwongwana, Fasai (Engineering, Technology & Applied Science Research, 2025)
Phototherapy devices play a crucial role in the treatment of neonatal jaundice in hospitals across Thailand. Adherence to appropriate standardized guidelines for phototherapy use is essential to ensure that treatment outcomes align with medical plans. This study highlights the importance of the engineering processes involved in preparing phototherapy devices prior to treatment. The findings reveal significant variations in irradiance levels of phototherapy devices during continuous use. It is recommended that the preparation process in hospitals should include regular monitoring of the irradiance levels from phototherapy devices. Establishing standardized protocols for preparation and ensuring strict implementation would not only enhance the overall effectiveness of phototherapy in treating neonatal jaundice but also contribute to the development of safer and more consistent treatment practices for infants.